Descriptions of the mature larva and pupa of Pseudopyrochroa facialis (Fairmaire) from Southwest China (Coleoptera: Pyrochroidae: Pyrochroinae), with redescriptions of adult stages and notes on natural history - Zhan, Zhihong; Liu, Yanchen; Young, Daniel K. (Zootaxa, 2022)
Larvae and pupae of Pseudopyrochroa facialis were collected beneath bark and in coarse, decaying woody debris of a standing, dead Cyclobalanopsis glauca tree in Guiyang City, Guizhou Province, China. The species association was confirmed by rearing both males and females to the adult stage. This represents the first record of a mainland Chinese species of Pseudopyrochroa to be reared in order to establish species association and identity. The mature larva and pupa are described and illustrated along with descriptions and illustrations of reared and additional adult males and females. Observations relating to the larval/pupal macro- and microhabitats and natural history are provided.